Regional bone mineral density in male athletes: a comparison of soccer players, runners and controls. Issue 10 (1st May 2007) - Fredericson, Michael; Chew, Kelvin; Ngo, Jessica; Cleek, Tammy; Kiratli, Jenny; Cobb, Kristin
Abstract : Objectives: To investigate the association of soccer playing and long-distance running with total and regional bone mineral density (BMD). Design: Cross-sectional study. Setting: Academic medical centre. Participants: Elite male soccer players (n = 15), elite male long-distance runners (n = 15) and sedentary male controls (n = 15) aged 20–30 years. Main outcome measurements: BMD (g/cm 2 ) of the lumbar spine (L1–L4), right hip, right leg and total body were assessed by dual-energy x -ray absorptiometry, and a scan of the right calcaneus was performed with a peripheral instantaneous x -ray imaging bone densitometer. Results: After adjustment for age, weight and percentage body fat, soccer players had significantly higher whole body, spine, right hip, right leg and calcaneal BMD than controls (p = 0.008, p = 0.041, p<0.001, p = 0.019, p<0.001, respectively) and significantly higher right hip and spine BMD than runners (p = 0.012 and p = 0.009, respectively). Runners had higher calcaneal BMD than controls (p = 0.002). Forty percent of the runners had T-scores of the lumbar spine between −1 and −2.5. Controls were similar: 34% had T-scores below −1 (including 7% with T-scores lower than −2.5). Conclusions: Playing soccer is associated with higher BMD of the skeleton at all sites measured. Running is associated with higher BMD at directly loaded sites (the calcaneus) but not at relatively unloaded sites (the spine). Specific loading conditions, seen in ball sports or in running, play a pivotal role in skeletal adaptation. The importance of including an appropriate control group in clinical studies is underlined.